Fistulizing Epstein–Barr virus‐positive plasmablastic lymphoma in an HIV‐positive man. (1st February 2016) - Rangel, J.; Novoa, R.; Morrison, C.; Frank, D.; Kovarik, C.
Summary: Plasmablastic lymphoma (PBL) is an unusual subtype of non‐Hodgkin lymphoma recently classified as a diffuse immunoblastic lymphoma with a plasma‐cell immunophenotype. Originally described in the oral cavity of HIV‐positive patients, it has also been recognized to occur rarely at other sites. We describe a previously unreported fistulizing presentation of Epstein–Barr virus (EBV)‐positive PBL, reviewing its association with HIV‐1 infection and its importance as an AIDS‐defining malignancy.